2006
DOI: 10.21273/hortsci.41.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sour Orange Accessions and Evaluation of Their Genetic Variability by Molecular Marker Analyses

Abstract: A collection of 18 accessions of sour orange (Citrus aurantium L.) coming from Sicily and other countries was investigated by two polymerase chain reaction (PCR)-based DNA marker technologies. Ten inter-simple sequence repeat (ISSR) primers and fi fteen randomly amplifi ed polymorphic DNA (RAPD) primers were used to identify and to evaluate the genetic variability and relationship of accessions. A total of 111 ISSR and 145 RAPD amplifi ed fragments were used to estimate the Dice's coeffi cient of similarity fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 42 publications
3
13
1
2
Order By: Relevance
“…ISSR markers technique has been known as a rapid, reproducible and useful method for distinguishing among different cultivars and clustering genotypes in the citrus species (Siragusa et al, 2006;Yang et al, 2010). In the present study, 13 primers produced clear, species-specific fingerprint patterns with all samples and were sufficient to discriminate varietal groups of citrus and produced results consistent with previous studies (Yang et al, 2010).…”
Section: Genetic Analysis Of the Citrus Genussupporting
confidence: 86%
“…ISSR markers technique has been known as a rapid, reproducible and useful method for distinguishing among different cultivars and clustering genotypes in the citrus species (Siragusa et al, 2006;Yang et al, 2010). In the present study, 13 primers produced clear, species-specific fingerprint patterns with all samples and were sufficient to discriminate varietal groups of citrus and produced results consistent with previous studies (Yang et al, 2010).…”
Section: Genetic Analysis Of the Citrus Genussupporting
confidence: 86%
“…On the other hand, the present result suggested that the rates of seedlings generating adventitious shoots in the cut end of epicotyls is genotype-specific, although the rates were different in three sour orange cultivars 'Kabusu', 'Zadaidai', and 'Variegated Daidai' (Table 2). Sour orange cultivars have been reported to be either genetically identical clones or sour orange hybrids (Siragusa et al, 2006). In the present study, the rates of decapitated seedlings generating adventitious shoots on the cut edge increased with increases in the length of epicotyls after decapitation.…”
Section: Discussionsupporting
confidence: 49%
“…'Goutou' and 'Zhuluan' were probably sour orange-pummelo hybrids used as rootstocks introduced from China, [39][40][41] and they were closely clustered with the true sour orange 'Sour' based on the SNP genotypic data, as well as fruit characteristics ( Fig. 4; see also Supporting information, Fig.…”
Section: Discussionmentioning
confidence: 99%